Finding extraterrestrial sites for thermophiles. (1st April 2004) - Naylor, T.
Abstract : Virtually our entire knowledge of the universe comes from two sorts of measurement of the electromagnetic radiation from the stars and galaxies within it; either their flux through relatively wide bandpasses (photometry), or measurements of the shape and wavelength of relatively narrow lines via spectroscopy. These techniques are now being used to discover planets outside our solar system, and perhaps in the next 10 years will begin to characterize them. If a serious search is to be made for extraterrestrial thermophiles, we need predictions for the effects of thermophiles on their host planets that are observable with these techniques. In this paper I shall outline what sorts of observation are likely to be used in the next 15 years for extra-solar planet work. All of the journal articles quoted here can be found through http://adsabs.harvard.edu/abstract_service.html, and often also accessed as preprints at http://uk.arxiv.org/form/astro%20ph?MULTI=form%20±%20interface .